CIVIL LIABILITY OF THE SUPERVISING PHYSICIAN FOR DAMAGES CAUSED TO PATIENTS IN MEDICAL SCHOOLS ABSTRACT (REMUNOM, 2025)
This study addresses the civil liability of the supervising physician for damages caused to patients in medical schools, with the aim of analyzing the legal implications of this responsibility within the context of medical academic training. The research was bibliographical in nature and covered the structure of civil liability, along with other outcomes related to the topic. The research problem involves defining the legal obligations of the supervising physician, considering their pedagogical role and responsibilities in supervising students during patient care. The methodology consisted of analyzing legal doctrines and relevant legislation on the civil liability of healthcare professionals in the academic environment. The study's relevance lies in highlighting the importance of ethically and legally grounded training, with the goal of protecting patient rights and preventing harm. The conclusion points to the need for greater clarity in legislation and educational protocols to ensure that the supervising physician’s civil liability is properly assigned and that patients are adequately protected.